Understanding urban sustainability through newspaper discourse: a look at Germany - Schwegler, Carolin (Journal of environmental studies and sciences, 2015)
The term sustainable city is semantically multi-faceted, encompassing or affiliated with numerous other, sometimes conflicting, conceptual designations. Aiming to balance economic development, high quality of life, and environmental protection, the path towards sustainable development has changed over time, new terms have been created and the meaning of familiar terms has changed. In addition, public media play an important role in forming opinions and constituting conceptual knowledge. On this account, changing terms, meanings, and influences have to be regarded carefully. This paper seeks to illuminate changes of meaning by differentiating and comparing various terminologies related to urban sustainability with regard to changing influences. It studies discourse related to sustainable city in newspapers during the sample period 1992-2013 and focuses on designations of urban sustainability that have appeared in the media in Germany—the country of the Energiewende (energy transition)—during the last two decades. The key findings concern changes in the use and the creation of terms and also changes of their meanings. The European city for instance has long been one of the additionally created terms in Germany, but its meaning in the media has shifted from lending geographical specificity to being synonymous with sustainable city in general. Despite the fact that urban sustainability suggests a specific regional scale, German national media create the impression that there is a limited set of concepts nowadays. This evokes an apparent consensus on a national level compared to the former (regional) diversity of terms and meanings. In this paper, the conceptualization that has been most influential recently in the German discourse, namely innovative or smart city, will furthermore be outlined. A possible reason for the strong emergence of these concepts in national discourses on urban sustainability is evaluated. Copyright AESS 2015
Published online: 4 October 2014
Gesehen am 22.07.2020